A Rare Case of a Solitary Fibrous Tumor of the Spermatic Cord. (22nd May 2021) - Awobajo, Moyosore; Hettwer, Stefanie; Hackman, Sarah
Abstract : Solitary fibrous tumors (SFTs) are rare mesenchymal tumors, originally identified in the pleura. Even though they have subsequently been described in several extrapleural sites, the incidence of SFTs in the spermatic cord is particularly rare. Here, we report a case of a 27-year-old male that presented with a 3-year history of left scrotal swelling. Computed tomography (CT) and ultrasound demonstrated multiple solid, hypoechoic well-circumscribed masses that were separate from the testis. Surgical excision of the mass led to pathologic diagnosis of a solitary fibrous tumor involving the spermatic cord. Solitary fibrous tumors, although rare, are an important differential diagnosis for urogenital tumors.